Biomethanation and microbial community changes in a digester treating sludge from a brackish aquaculture recirculation system. (August 2016) - Zhang, Xuedong; Tao, Yu; Hu, Jianmei; Liu, Gang; Spanjers, Henri; van Lier, Jules B.
Highlights: Saline seed & stepwise increased OLR enhance specific CH4 yield from salty sludge. Stable digester performance w/o severe VFA accumulation even at 4.4 kg COD/(m 3 day). OLR adjustment & fecal substrate substantially influence the digester microbiomes. Most abundant methanogen is Methanosarcina in both the inoculum and digestates. Increasing similarity in microbial community of inoculum and digestates at low OLR. Abstract: Using a high-salinity-adapted inoculum and a moderate stepwise-increased organic loading rate (OLR), a stable digester performance was achieved in treating sludge from a brackish aquaculture recirculation system. The specific methane yield was distinctly enhanced, reaching 0.203 L CH4 /g CODadded, compared to literature values (0.140–0.154 L CH4 /g CODadded ) from the salty sludges. OLR adjustment and the fecal substrate substantially influenced population changes in the digester. Within the bacterial subpopulations, the relative abundance of Bacillus and Bacteroides declined, accompanied by the increase of Clostridium and Trigonala over time. The results show Trigonala was derived from the substrate and accumulated inside the digester. The most abundant methanogen was Methanosarcina in the inoculum and the digestates. The Methanosarcina proliferation can be ascribed to its metabolic versatility, probably a feature of crucial importance for high-salinity environments. Other frequently observed methanogens were outcompeted. The population similarity at the genus level between inoculum and digestates declined during the initial stage and afterwards increased.